Principles of thermal analysis and calorimetry - Gaisford, Simon; Kett, Vicky; Haines, P. J. (Royal Society of Chemistry, 2016)
This book supplies an up to date, concise and readable account of the principles, experimental apparatus and practical procedures used in thermal analysis and calorimetric methods of analysis and will be an aid for students and lecturers through to industrial and laboratory staff and consultants.